2020
DOI: 10.1007/s11912-020-00979-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Outpatient Cancer Rehabilitation Can Improve Cancer Patients’ Physical and Psychosocial Status—a Systematic Review

Abstract: Purpose of Review This systematic review aimed to determine the effects of interdisciplinary/multidisciplinary outpatient rehabilitation programmes by looking at physical, psychosocial and return to work status of adult cancer patients. Recent Findings There is growing evidence that emphasizes the importance of interdisciplinary/multidisciplinary rehabilitation especially in outpatient care, which addresses the complex and individual needs of cancer patients. Many studies focus on measuring the effect of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…Rehabilitation interventions should be tailored using a stepped care approach according to need, differing levels of comorbidities, and impairment. 69 A Cochrane review (13 RCTs, 1669 participants) 70 and a review (six RCTs, 682 participants) 71 of multidimensional outpatient rehabilitation programmes showed positive effects on quality of life, physical and emotional functioning, and return to work. Exercise interventions can lead to improvement in physical capacity and cardiorespiratory fitness, can improve fatigue and depression, 72 and could improve survival.…”
Section: Comprehensive Multidisciplinary Rehabilitationmentioning
confidence: 99%
“…Rehabilitation interventions should be tailored using a stepped care approach according to need, differing levels of comorbidities, and impairment. 69 A Cochrane review (13 RCTs, 1669 participants) 70 and a review (six RCTs, 682 participants) 71 of multidimensional outpatient rehabilitation programmes showed positive effects on quality of life, physical and emotional functioning, and return to work. Exercise interventions can lead to improvement in physical capacity and cardiorespiratory fitness, can improve fatigue and depression, 72 and could improve survival.…”
Section: Comprehensive Multidisciplinary Rehabilitationmentioning
confidence: 99%
“…This is consistent with previous studies in which CIPN patients with caregivers experienced psychological distress due to forced caregiving[ 23 ], cancer survivors who return to work, and reduced overtime hours had improved overall quality of life[ 24 ], and patients with higher levels of education are likely to be more understanding and cooperative with treatment[ 25 ]. The study showed that multidisciplinary outpatient rehabilitation programs consisting of exercise intervention, psychotherapy, information support and professional counseling with each other can improve the physical and or psychosocial status of cancer survivors[ 26 ].Our study further demonstrates the psychosocial burden of CIPN patients in the post-chemotherapy setting. Therefore, more high-quality multidisciplinary supportive care needs to be sought to help CIPN patients cope with post-chemotherapy toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have shown that interventions using a biopsychosocial model can significantly improve the quality of life of patients. Biological, psychological and social–environmental factors can improve clinical outcomes, especially for pain management after cancer, and individual factors should not be underestimated[ 26 ]. Another study showed that the level of adaptation of CIPN patients influenced individual coping styles and behavioral patterns[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses indicate that multidisciplinary interventions, consisting of both physical and psychosocial components, have positive effects on fatigue and physical function in BC survivors (Myrhaug et al 2018;Scott 2013). A recent systematic review also indicated that multidisciplinary outpatient programs in different cancer types improve physical and psychosocial outcomes (Kudre et al 2020). Moreover, studies have demonstrated positive effects of exercise programs in BC populations after treatment on fatigue, muscle strength, cardiorespiratory fitness, physical function, and HRQoL (Campbell et al 2019;Lahart et al 2018).…”
Section: Introductionmentioning
confidence: 99%